Influence of the Various Deformation Modes on Rheology of High-Concentrated Magnetorheological Fluids of Complex Composition for Controlled Layered Structures - Korobko, Evguenia; Zhurauski, Mikalai; Novikova, Zoya (Frontiers in Materials, 2019)
The results of an experimental study of the rheological behavior of highly concentrated magnetorheological fluids of complex composition containing the main magnetosensitive filler –carbonyl iron and additives – particles of aerosil, chromium dioxide, and bentonite clay are presented. The modes of continuous shear deformation, linear increase of shear stress, and harmonic shear oscillations are considered. The influence of the additive material on shear stress, yield stress, components of the complex shear modulus of magnetorheological fluids in a magnetic field is determined.